Penguatan Posyandu Terintegrasi Asuhan Keperawatan Komplemeter dan Olah Raga Senam Sehat Lansia - Reflianto, Reflianto; Syamsuar, Syamsuar; Ariani, Farida; Wandi, Joni Indra; Afnita, Nora (Institut Agama Islam Sumatera Barat, 2025)
This community service activity aimed to enhance the healthy quality of life of the elderly in Nagari Sungai Buluh, Batang Anai Subdistrict, Padang Pariaman Regency, by preventing degenerative diseases. The program employed a community-based research approach, incorporating complementary nursing care based on traditional medicine and elderly exercise programs. Its primary objectives were to establish a Healthy Family Community through an integrated Posyandu (health post), promote healthy exercise among the elderly, and empower Posyandu cadres to advocate for healthy living behaviors and regular health check-ups for the elderly. The results indicated an improvement in the community's health status and knowledge about maintaining a healthy family through complementary nursing care and elderly exercise programs. The initiative also successfully raised awareness about the importance of health and complementary care for the elderly, including exercise guidance and health check-ups. Furthermore, the activity provided health check-up services for toddlers in the foster village. The integration of complementary nursing care and elderly exercise programs within the Posyandu framework proved effective in improving the health and well-being of the elderly in Nagari Sungai Buluh.